2022
DOI: 10.1002/ppul.26061
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound findings in asymptomatic healthy children with asthma

Abstract: Background Lung ultrasound (LUS) has been shown to be an effective tool to rapidly diagnose certain causes of pediatric respiratory distress. However, very little is known about LUS findings in pediatric asthma. Objectives The primary objective of this study was to characterize LUS findings in a cohort of pediatric patients with a definitive diagnosis of asthma, outside of an asthma exacerbation. Methods Eligible patients, aged 6−17 years old and diagnosed with asthma, underwent LUS during an outpatient visit.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…We also found a moderate correlation between pleural line slope and excursion. Subpleural infiltrates on POCUS were consistent with those in asthmatic children described elsewhere 8 …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We also found a moderate correlation between pleural line slope and excursion. Subpleural infiltrates on POCUS were consistent with those in asthmatic children described elsewhere 8 …”
Section: Discussionsupporting
confidence: 84%
“…Subpleural infiltrates on POCUS were consistent with those in asthmatic children described elsewhere. 8 In a child without lower airway obstruction, the relationships between the ultrasound probe, chest wall and pleura are consistent throughout the respiratory cycle, resulting in the flat tracing of the pleural line. In a child with lower airway obstruction and increased respiratory effort, the peaks of pleural retraction can be appreciated both qualitatively and quantitatively.…”
Section: Discussionmentioning
confidence: 99%
“…Marzook et al performed lung ultrasounds in six lung zones for children aged 6–17 years with symptomatic and asymptomatic asthma in an outpatient clinic visit. In this prospective, cross‐sectional study, the authors found that 19% of children with asthma had evidence of a lung artifact, with a predominance in the right anterior and lateral lung zones 3 . Importantly, there was no association between presence of an artifact and asthma control or severity.…”
Section: Diagnosis and Evaluationmentioning
confidence: 85%
“…In this prospective, cross-sectional study, the authors found that 19% of children with asthma had evidence of a lung artifact, with a predominance in the right anterior and lateral lung zones. 3 Importantly, there was no association between presence of an artifact and asthma control or severity. For optimal comparison, further investigation is needed to understand baseline lung ultrasounds in healthy children.…”
mentioning
confidence: 94%
“…The main ultrasound findings in children with asthma are B lines, pulmonary consolidations, and/or pleural abnormality. These artifacts can be seen both outside of acute exacerbations [43] and during exacerbations. In particular, Dankoff et al showed that pathologic lung ultrasound scans performed in asthmatic patients accessing the emergency department were related to increased antibiotic use, prolonged length of stay in the emergency department, and increased rate of hospitalization [44].…”
Section: Asthmamentioning
confidence: 99%